An iPSC model for POLR3A-associated spastic ataxia: generation of three unrelated patient cell lines - Manibarathi, Kalaivani; Pham, Tam; Hengel, Holger; Synofzik, Matthis; Nagel, Maike; Schüle-Freyer, Rebecca (Stem cell research, 2024)
Spastic Ataxias (SA) are a group of neurodegenerative disorders with combined pyramidal and cerebellar system affection, leading to an overlap phenotype between Hereditary Spastic Paraplegias (HSP) and Cerebellar Ataxias (CA). Here we describe the generation of iPSCs from three unrelated patients with an ultra-rare subtype of SA caused by compound heterozygous mutations in POLR3A, that encodes the largest subunit of RNA polymerase III. iPSCs were reprogrammed from normal human dermal fibroblasts (NHDFs) using episomal reprogramming with integration-free plasmid vectors: HIHRSi004-A, derived from a 44 year-old male carrying the mutations c.1909 + 22G > A/c.3944_3945delTG, HIHRSi005-A obtained from a 66 year-old male carrying the mutations c.1909 + 22G > A/c.1531C > T, and HIHRSi006-A from a 27 year-old male carrying the mutations c.1909 + 22G > A/c.2472_2472delC (ENST00000372371.8).
Gesehen am 15.11.2024